An approach to service innovation in real estate through information technology. (6th August 2010) - Stevens, David P.; Zhu, Zhiwei
Service industries now comprise the majority of the workforce in developed countries. Service innovation provides a mechanism for economic growth, especially in industries which have not yet taken advantage of information technology and related tools and concepts. The residential real estate market in the USA lacks an adopted data standard and is an example of such an industry. This paper describes the limitations and inefficiencies of the current system, and presents two design elements of a new system that leverages the consumer's participation in the delivery of services and produces significant economic benefits through the innovation.